Distribution patterns, history, and dynamics of peatland vascular plants in Pomerania (NW Poland) - Sotek, Zofia (Biodiversity: Research and Conservation, 2011)
Pomerania is rich in various peatlands (fens, transitional bogs, raised bogs, spring-water mires, etc.), which support many rare and threatened plant species. This study was aimed: (1) to determine the phytogeographic diversity of Pomeranian peatland vascular plants associated with the classes Oxycocco-Sphagnetea and Scheuchzerio-Caricetea nigrae; (2) to attempt a reconstruction of the history of their postglacial migrations; and (3) to assess the dynamic trends of selected species. A database of records of 83 Pomeranian peatland plants was created, and cartograms of their distribution in Pomerania were made. Each taxon was briefly described, considering its distribution, phytocoenotic spectrum, and biological properties (e.g. pollination mode, diaspores dispersal). The phytogeographic analysis took into account geographic and directional elements, as well as mountain species found in Pomeranian peatlands. The plants' potential for colonization of new sites was assessed on the basis of Raunkiaer's life forms, modes of pollination and seed dispersal, and types of life strategies. As a result of numerical analysis and visual comparison of cartograms, 5 regional distributional types were distinguished: western, northern, eastern, all-Pomeranian, and disjunct. Within the eastern and all-Pomeranian types, which showed internal variation, several subtypes were distinguished. Most of the considered climatic variables (growing season length, temperature, and precipitation variables) were found to affect significantly the floristic variation of Pomeranian peatlands. The available palaeobotanical, palaeoclimatic, palaeoecological, and phytogeographic data, as well as original field research on the distribution of the taxa, allowed the formulation of hypotheses on the time and directions of their migration into Pomerania. Moreover, dynamic trends of selected species are analysed, and the decline of many peatland plant species in Pomerania is discussed.